A Prospective Study Comparing Billroth II and Roux-en-Y Gastrojejunostomy in Patients with Carcinoma Stomach - Ravella Vishnu Prasad; Dash Nihar Ranjan; Samantaray Satya Prasad; Pal Sujoy; Sahni Peush (National Board of Examinations Journal of Medical Sciences, 2023)
Aims and objectives: Comparison of the outcome of Roux-en-Y & Billroth II gastrojejunostomy in patients with gastric cancer specifically in terms of nutrition, gastric emptying and quality of life. Methods: All good performance status patients (ECOG ≤2) aged less than 75 years old with distal gastric carcinoma presenting to the Department of GI Surgery, AIIMS, New Delhi between November 2012 and December 2013 were evaluated prospectively for inclusion in the study. Roux-en-Y gastrojejunostomy or Billroth II gastrojejunostomy was planned after distal gastrectomy and Billroth II gastrojejunostomy only in unresectable patients. Assessment was done 3 months after surgery. Results: Thirty patients were recruited in the study. Twenty-four patients were offered distal resection. Roux-en-Y reconstruction was done in 16 patients & Billroth II reconstruction in 8 patients. Six unresectable cases were offered palliative Billroth II bypass only. Comparison of Roux-en-Y vs Billroth II gastrojejunostomy revealed following results. In the postoperative period, mean duration of nasogastric tube drainage and mean onset of regular oral diet were 3±0.8 days vs 4.5±2 days and 6.2±2.2 days vs 8.8±3.9 days respectively. At 3 months of follow up, physical parameters of WHOQOL-BREF assessment revealed score of 10.2±1.4 vs 8.2±2.5 respectively. Conclusion: Reconstruction in patients with gastric cancer in the form of Roux-en-Y & Billroth II gastrojejunostomy revealed favourable short-term results like removal of nasogastric tube drain and initiation of enteral nutrition; and physical parameters of quality of life at the end of the third month. Rest of the results were similar in both groups.